Deteksi Dini Kanker Pada Anak - Lina Mahayaty; Ethyca Sari; Budi Artini; Wijar Prasetyo; Retty Nirmala Santiasari (Pelita Abdi Masyarakat, 2022)
Background: Cancer is a malignant disease that often causes death. Not only attacks adults, cancer also attacks children. The death rate is more than 50 percent. The high mortality rate in children due to cancer can be caused by parents' ignorance of the symptoms of the disease. The purpose of community service activities is to increase the knowledge of PKK mothers who have children aged 3-5 years about early detection of cancer in children in Puri Menganti Indah Housing, Wonokoyo District, Gresik Regency. Method : This counseling is carried out using the lecture method using power point media and leaflets Result: This outreach activity is running optimally, marked by an increase in respondents' understanding. Based on the results, it was found that 19 people had less knowledge (65%) while after education there were 23 people (79%) very good knowledge and 6 people (21%). Conclusion: Health education activities on Early Detection of Cancer in Children can continue to be carried out to improve knowledge of PKK mothers in Puri Menganti Indah Housing, Wonokoyo District, Gresik Regency